Produccion masiva y uso de parasitoides para el control biologico de la broca del cafe en Colombia - Bustillo P.A.=700 1 Orozco H, J.; Benavides M, P.; Portilla R, M.
(Es, En)
Ilus., 22 ref.
Keywords: COFFEA ARABICA; HYPOTHENEMUS HAMPEI; CONTROL BIOLOGICO; PARASITOIDES; CRIA MASIVA; COLOMBIA; CEPHALONOMIA STEPHANODERIS; PROROPS NASUTA; LIBERACIONES